2022
DOI: 10.1155/2022/9190241
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Analysis of 85 Cases of External Auditory Canal Cholesteatoma Surgery under Specialized Endoscopy

Abstract: Objective. To investigate the clinical characteristics, surgical experience, and surgical outcomes of external auditory canal cholesteatoma (EACC) surgery under endoscopic otolaryngoscopy. Methods. A retrospective analysis of 85 EACC cases admitted to the Department of Otolaryngology, Renji Hospital, Shanghai Jiaotong University School of Medicine, from January 2016 to February 2021 was performed, followed by retrospective analysis of clinical data to explore the feasibility and clinical characteristics of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Tomography 2023, 9, FOR PEER REVIEW 5 40 and 70 years of age. It is defined as a cystic mass of skin debris and cholesterol crystals that obstructs the EAC [27].…”
Section: Cholesteatoma Of the External Ear Canalmentioning
confidence: 99%
See 3 more Smart Citations
“…Tomography 2023, 9, FOR PEER REVIEW 5 40 and 70 years of age. It is defined as a cystic mass of skin debris and cholesterol crystals that obstructs the EAC [27].…”
Section: Cholesteatoma Of the External Ear Canalmentioning
confidence: 99%
“…The principles of treatment for EACC are complete resection, ideally maintaining the normal structure and function of the EAC [27]. Histopathologically, keratinized squamous epithelium can be found along the EAC and signs of local invasion with bony destruction, wandering erosions, and periostitis can be present [28,29].…”
Section: Cholesteatoma Of the External Ear Canalmentioning
confidence: 99%
See 2 more Smart Citations
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%